Research Progress of Chinese Herbal Medicine Intervention in Renal Interstitial Fibrosis - Liu, Xiao-Yuan; Zhang, Xu-Bin; Zhao, Ya-Feng; Qu, Kai; Yu, Xiao-Yong (Frontiers in Pharmacology, 2022)
Chronic kidney diseases usually cause renal interstitial fibrosis, the prevention, delay, and treatment of which is a global research hotspot. However, no definite treatment options are available in modern medicine. Chinese herbal medicine has a long history, rich varieties, and accurate treatment effects. Hitherto, many Chinese herbal medicine studies have emerged to improve renal interstitial fibrosis. This paper reviews the mechanisms of renal interstitial fibrosis and recent studies on the disease intervention with Chinese herbal medicine through literature search, intend to reveal the importance of Chinese herbal medicine in renal interstitial fibrosis. The results show that Chinese herbal medicine can improve renal interstitial fibrosis, and the effects of Chinese herbal medicine on specific pathological mechanisms underlying renal interstitial fibrosis have been explored. Additionally, the limitations and advantages of Chinese herbal medicine in the treatment of renal interstitial fibrosis, possible research directions, and new targets of Chinese herbal medicine are discussed to provide a basis for studies of renal interstitial fibrosis.